1964
DOI: 10.1017/s0068245400006031
|View full text |Cite
|
Sign up to set email alerts
|

The Wool Industry of Crete in the Late Bronze Age

Abstract: In this paper the writer examines the largest group of Linear B tablets from Knossos, the great archive of records dealing with sheep. The results of this inquiry provide, it is suggested, a plausible solution to a long-standing problem, the source of the wealth of Knossos in the Late Bronze Age.The account of the great archive of sheep records from Knossos (Series D) which Ventris and Chadwick present in Documents in Mycenaean Greek remains the most influential treatment of this series taken as a whole, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 2 publications
0
21
0
3
Order By: Relevance
“…In their review of the ethology of free-ranging domestic animals, Arnold & Dudzinski (1978) make only passing reference to wethers, and they have not been the subject of any previously published studies of behaviour. Yet wethers have been of very great importance in animal husbandry from ancient times (Trow-Smith, 1957;Killen, 1964), through the Middle Ages (Lloyd, 1977-78;Ryder, 1983) and on into the present century (Fraser & Stamp, 1957). Even today, on the island of North Ronaldsay in Orkney, where the sheep are traditionally confined to the foreshore (Hall, 1975) and eat only seaweed, I have observed that a high proportion of the sheep are wethers and serve as a 'walking larder' (J.…”
Section: Discussionmentioning
confidence: 99%
“…In their review of the ethology of free-ranging domestic animals, Arnold & Dudzinski (1978) make only passing reference to wethers, and they have not been the subject of any previously published studies of behaviour. Yet wethers have been of very great importance in animal husbandry from ancient times (Trow-Smith, 1957;Killen, 1964), through the Middle Ages (Lloyd, 1977-78;Ryder, 1983) and on into the present century (Fraser & Stamp, 1957). Even today, on the island of North Ronaldsay in Orkney, where the sheep are traditionally confined to the foreshore (Hall, 1975) and eat only seaweed, I have observed that a high proportion of the sheep are wethers and serve as a 'walking larder' (J.…”
Section: Discussionmentioning
confidence: 99%
“…There are ample historical suggestions of fine-woolled sheep in the area to support the view that the legend refers to a search for a fine-woolled breed of sheep (Ryder 1983). Killen (1964), for instance, thought that the story of Jason's voyage might be an echo of efforts of mainland Greece to discover new sources of wool in the Black Sea area after about 1400 BC, when Knossos the supplier of wool from Crete had fallen. Ryder and Hedges (1973) reported on the first archaeological evidence of apparent fine wool in the Black Sea area.…”
Section: Piggottmentioning
confidence: 99%
“…If the theory (Gamble 1979, 132f.) that the inhabitants of Melos abandoned large tracts of the island to sheep-rearing in order to provide wool for export cannot be proved, there is clear evidence that the palace at Knossos exercised some sort of monopoly over wool, which was produced in sufficient quantities to suggest the possibility that the textile trade in Crete in LM I1 was export-oriented (Killen 1964). Finley also accepts that the wool helped to pay for imports (1970,39).…”
Section: Networkmentioning
confidence: 99%